Model for a vehicle dynamics through a sequence of traffic lights (2014)
In this paper we present an overview of a vehicular traffic model and its simulation, this model is characterized by a single vehicle traveling through a sequence of traffic lights that turn on and off with a specific frequency. The model includes three main dynamical modes, accelerated, decelerated and null state. We will show the description of the mathematical modeling used to simulate the system. The simulation was developed under an event driven strategy and implemented in Matlab. Regarding to the numerical analysis, we built a bifurcation diagram where the parameter under variation is the cycle of traffic lights. As a principal result, we evidence the effects of the cycle of traffic lights in the dynamical behavior of the system.